Molecular Detection of Bartonella spp. in China and St. Kitts - Ke Huang; Patrick John Kelly; Jilei Zhang; Yi Yang; Weiguo Liu; Anwar Kalalah; Chengming Wang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Bartonella are vector-borne hemotropic bacteria that infect a wide variety of hosts, including people. While there are PCR assays that can identify individual or groups of Bartonella, there is no reliable molecular method to simultaneously detect all species while maintaining genus specificity and sensitivity. By comparing highly conserved 16S rRNA sequences of the better-recognized Bartonella spp. on GenBank, we selected primers and probes for a genus-specific pan-Bartonella FRET-qPCR. Then, a gltA-based Bartonella PCR was established by selecting primers for a highly variable region of gltA, of which the sequenced amplicons could identify individual Bartonella spp. The pan-Bartonella FRET-qPCR did not detect negative controls (Brucella spp., Anaplasma spp., Rickettsia spp., Coxiella burnetii, and Wolbachia) but reliably detected as few as two copies of the positive control (Bartonella henselae) per reaction. There was complete agreement between the pan-Bartonella FRET-qPCR and the gltA-based Bartonella PCR in detecting Bartonella in convenience test samples from China and St. Kitts: cats (26%; 81/310), Ctenocephalides felis (20%; 12/60), cattle (24%; 23/98), and donkeys (4%; 1/20). Sequencing of the gltA-based Bartonella PCR products revealed B. henselae (70%; 57/81) and B. clarridgeiae (30%; 24/81) in cats and C. felis (67%; 8/12, and 33%; 4/12, respectively) and B. bovis in cattle (23.5%; 23/98) and donkeys (4.0%; 1/24). The pan-Bartonella FRET-qPCR and gltA-based Bartonella PCR we developed are highly sensitive and specific in detecting recognized Bartonella spp. in a single reaction. The pan-Bartonella FRET-qPCR is convenient requiring no gel electrophoresis and providing copy numbers, while the gltA-based Bartonella PCR reliably differentiates individual Bartonella species. The use of these PCRs should greatly facilitate large-scale surveillance studies and the diagnosis of infections in clinical samples.